2023
DOI: 10.1002/jcla.24865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the diagnostic and prognostic value of serum TuM2‐PK, NSE, and ProGRP in small cell lung cancer

Abstract: Lung cancer is one of the most common malignancies in the world, accounting for 13% of all cancers. 1 SCLC accounts for 15%-18% of all lung cancers. 2 More than half of SCLC patients are in the extensive stage of the disease at the time of diagnosis. Despite systematic treatment, the overall 5-year survival rate for SCLC remains below 15%. 3 Therefore, it is necessary to seek novel biomarkers in order to diagnose and predict the progress of SCLC. The ProGRP and NSE are common tumor markers in the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown the high sensitivity of ProGRP in the diagnosis of SCLC, especially when utilized in combination with established tumor markers such as NSE and CYFRA21-1. 21,22 Combined detection typically enhanced overall diagnostic reliability compared to individual biomarkers due to the complementary nature of different indicators, a consensus supported by most of the previous reports. 23,24 Our study revealed that the combined detection of all six biomarkers yielded an impressive AUC ranging from 0.937 to 0.998 in diagnosing the three subtypes of LC, coupled with a high specificity of 98.0% (Table 3).…”
Section: Discussionmentioning
confidence: 72%
“…Numerous studies have shown the high sensitivity of ProGRP in the diagnosis of SCLC, especially when utilized in combination with established tumor markers such as NSE and CYFRA21-1. 21,22 Combined detection typically enhanced overall diagnostic reliability compared to individual biomarkers due to the complementary nature of different indicators, a consensus supported by most of the previous reports. 23,24 Our study revealed that the combined detection of all six biomarkers yielded an impressive AUC ranging from 0.937 to 0.998 in diagnosing the three subtypes of LC, coupled with a high specificity of 98.0% (Table 3).…”
Section: Discussionmentioning
confidence: 72%
“…In the study in which Li Li et al 20 analyzed the diagnostic and prognostic values of serum TuM2-PK, NSE and ProGRP values in small cell lung cancer, it was shown that M2-PK, NSE and ProGRP levels were higher than the control groups with benign lung disease and healthy control groups. Tu M2 PK sensitivity was found to be 82.35% and serum Tu M2 PK level may be an effective marker of small cell lung cancer and an independent prognostic factor for shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…A study from 2023 from China reported that ProGRP levels in patients with SCLC were higher than in the healthy control group ( p < 0.05) and in the benign lung disease group ( p < 0.05); the sensitivity and specificity of ProGRP was estimated at 77.45% and 86.67%, respectively [ 38 ].…”
Section: Discussionmentioning
confidence: 99%